FORMULATION AND EVALUATION OF NANOSTRUCTURED LIPID CARRIERS BASED CAPSULE - Karan K. Lokhande; Pranali P. Malusare
The objective of this investigation was to formulate an ideal nanostructured lipid carrier (NLC) for glibenclamide in oral capsules. Employing factorial design, the NLC formulation was achieved through high-pressure homogenization using Design-Expert® software, optimized using a 32 -factor experimental design and response surface analysis. Comprehensive analyses were conducted to characterize NLCs and determine the optimal formulation. Rigorous evaluations, including drug content, in vitro diffusion and stability studies, were performed. Safety assessments, efficacy studies and optimization led to the identification of an optimal NLC formulation with specific lipid and surfactant percentages, resulting in a desirable particle size (nm) and a robust zeta potential indicative of strong physical stability.